Examining the effect of categorized versus uncategorized homework on test performance of general chemistry students - Cox Charles T.; Gulacar Ozcan (Chemistry Teacher International)
The study reports a comparison of two first-semester general chemistry cohorts who were provided with the same instruction and course materials, but the format for their online homework assignments differed. One cohort had homework assignments organized using a block or categorized format, in which the concepts (e.g., limiting reagents) being assessed were identified for each problem. The second cohort had homework assignments organized using an uncategorized or interleaved format in which the assessed concepts were not provided. The two cohorts completed the same tests and a standardized American Chemical Society (ACS) final exam. Students who completed the uncategorized or interleaved homework assignments scored higher than the block or categorized cohort on each of the four tests and the final exam. Statistical differences, using a 95 % confidence level, were observed on the first test and final exam.